2022
DOI: 10.3389/fmed.2022.833965
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Accidental Death Among Women With Primary Ovarian Cancer: A Population-Based Study

Abstract: BackgroundWomen with ovarian cancer had the highest suicidal rate among all patients with gynecological malignancies, but no large studies about suicide and accidental death for women with ovarian cancers in detail were conducted. We aimed to determine the relative risk of suicide and accidental death among patients with ovarian cancer to that of the general population, and to identify risk factors associated with suicide and accidental death.MethodsData are from the SEER (surveillance, epidemiology, and end r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
1
16
1
Order By: Relevance
“…The observed number of HD deaths represented the total number of deaths from heart events in sarcoma patients during the follow-up period; the expected number of deaths represented the number of deaths from heart events in the general population with a similar age at diagnosis, sex, race, and calendar year distribution. Five-year age categories and three-year calendar categories were used for standardization ( 21 ). Mortality from fatal HD was calculated as the number of deaths from HD divided by person-years at risk ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…The observed number of HD deaths represented the total number of deaths from heart events in sarcoma patients during the follow-up period; the expected number of deaths represented the number of deaths from heart events in the general population with a similar age at diagnosis, sex, race, and calendar year distribution. Five-year age categories and three-year calendar categories were used for standardization ( 21 ). Mortality from fatal HD was calculated as the number of deaths from HD divided by person-years at risk ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…These include sexual dysfunction ( Rizzuto et al, 2021 ), fertility loss ( Carter et al, 2013 ), menopausal syndrome ( Gernier et al, 2021 ), body image disorders ( Brederecke et al, 2021 ), etc. The high malignancy and adverse outcomes of ovarian cancer may place patients at high suicide risk ( Chen et al, 2022 ). A study based on the SEER database reported a suicide rate of 13.92 per 100,000 person-years between 1973 and 2017, with a relative risk of 1.9 for women with ovarian cancer compared with the general population ( Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The high malignancy and adverse outcomes of ovarian cancer may place patients at high suicide risk ( Chen et al, 2022 ). A study based on the SEER database reported a suicide rate of 13.92 per 100,000 person-years between 1973 and 2017, with a relative risk of 1.9 for women with ovarian cancer compared with the general population ( Chen et al, 2022 ). Extensive literatures have confirmed that the suicide risk of ovarian cancer is highest in patients with gynecological malignancies ( Mahdi et al, 2011 ; Tang et al, 2016 ; Violette et al, 2019 ; Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations